The Relationship of Father Involvement with Self-Control in Adolescents Dating in Regency X - Nadhifa, Irsawinda; Fikry, Zulian (Universitas Pahlawan Tuanku Tambusai, 2024)
The adolescent phase is indicated by the stage of having reached the maturity of the sexual organs, causing attraction to the opposite sex which can be manifested in dating behavior. Self-control is important for adolescents who are dating, if they don’t have good self-control, adolescents cannot regulate and direct their behaviors so that they are vulnerable to deviant behavior including channeling sexual desires in dating. Self-control is influenced by father involvement. The objective of the research is to see the correlation between father involvement and self-control in adolescents who are dating in Regency X. The research employed a quantitative correlational approach. The sampling technique is snowball sampling with the number of research participants as many as 151 teenagers who are dating. In this study, the data analysis technique used the product moment correlation test developed by Karl Pearson. The results revealed that there is a significant positive correlation between father involvement and self-control in adolescents dating in Regency X with a correlation coefficient value of 0.550. Keyword: Father Involvement, Self-Control, Adolescent